Mixed community biofilms and microbially influenced corrosion - Marsili, Enrico (2019)
Metals are used in most marine infrastructures for energy extraction and production. Metal corrosion is a serious concern, due to the environmental, safety, and replacement costs associated with it. Microbially influenced corrosion (MIC) contributes to the overall corrosion process, through several chemical, electrochemical and biochemical mechanisms, particularly in the presence of microbial biofilms. In this short article, we discuss briefly recent advances in MIC research, comparing corrosion in single species and mixed species biofilms, and outline possible strategies for biofilm and corrosion control.